The Fate of Resectable Pancreatic Adenocarcinoma After Neoadjuvant Chemotherapy. Issue 1 (January 2022) - Irfan, Ahmer; Rose, J. Bart; Wang, Thomas N.; Vickers, Selwyn M.; Dudeja, Vikas; Gbolahan, Olumide; Reddy, Sushanth
Abstract : Objectives: Pancreatic cancer continues to be a major cause of cancer-related mortality. There has been a greater implementation of up-front chemotherapy for pancreatic adenocarcinoma patients. Although there are many theoretical benefits to neoadjuvant chemotherapy, its clinical impact is uncertain. We sought to understand the outcomes of patients with resectable and borderline-resectable pancreatic adenocarcinoma who underwent neoadjuvant chemotherapy. Methods: Patients were collected in a secure database from September 2018 to May 2020. Patients were excluded if they presented with locally advanced or metastatic disease, inability to complete chemotherapy, or if they were not a surgical candidate. Results: Sixty-six patients with resectable disease underwent chemotherapy. Folinic acid/5-fluorouracil/irinotecan/oxaliplatin was used in 41 patients (62.1%) and gemcitabine-based regimens in 28 patients (42.4%, greater than 100% as some patients underwent both regimens). After restaging, 47 patients (71.2%) were thought to have resectable disease. Of these patients, 36 have been successfully resected to date. Metastatic disease was found in 12 patients (18.2%) and 6 patients (9.1%) had locally advanced disease. Conclusions: Most patients with resectable pancreatic cancer are resected after neoadjuvant chemotherapy, but a subset will develop local or distant progression. Further studies will be needed to determine which patients will progress locally and may benefit from an up-front surgical approach.